Prenatal representations, early family relationships and child social-emotional development: The Father’s contribution - Lindstedt, Johanna (fi=Turun yliopisto|en=University of Turku|, 2024)
Family relationships begin to develop during pregnancy and provide the context for a child’s early social-emotional development. However, the contribution of parental prenatal representations and early parent–child relationships, particularly those of fathers, are less studied. This thesis examined the associations between fathers’ and mothers’ prenatal representations, early parent–child interaction, triadic family interaction, and the early social-emotional development of children in two-parent families, with particular emphasis on early father–child relationships. The data were collected as part of the multidisciplinary Steps to the Healthy Development and Well-being of Children cohort study. Families (n = 153) were followed from pregnancy until the child was 18 months old. The aims of this thesis were to examine 1) associations between fathers’ prenatal representations and postnatal father–child interaction (Study I), 2) the change and stability in father–child interaction from infancy to toddlerhood (Study I), 3) associations between dyadic parent–child interaction and triadic family interaction (Study II), and 4) fathers’ and mothers’ prenatal representations and their associations with a child’s social-emotional development (Study III). The results showed that fathers’ balanced prenatal representations were associated with higher quality in early father–child interaction. Both positive changes and moderate stability in dyadic father–child interaction were observed from infancy to toddlerhood. Well-functioning parent–child interaction, particularly between fathers and children, was associated with higher family coordination and cooperative family alliance in toddlerhood. In addition, both parents’ balanced prenatal representations were associated with higher social-emotional competence in children. The findings of this thesis highlight the importance of balanced prenatal representations and well-functioning early parent–child relationships. Both father–child and mother–child relationships play essential roles in shaping triadic family interaction and enhancing a child’s early social-emotional competence.

Raskausajan mielikuvat, varhaiset perhesuhteet ja lapsen sosioemotionaalinen kehitys: Isän merkitys Perhesuhteet alkavat kehittyä jo raskausaikana luoden puitteet lapsen varhaiselle sosioemotionaaliselle kehitykselle. Vanhempien raskaudenaikaisten mielikuvien ja varhaisten vanhempi-lapsisuhteiden merkitystä on tutkittu kuitenkin vasta vähän, erityisesti isien osalta. Tässä väitöskirjassa tutkittiin isien ja äitien raskaudenaikaisten mielikuvien, varhaisen vanhemman ja lapsen välisen vuorovaikutuksen, perheen triadisen vuorovaikutuksen ja lapsen sosioemotionaalisen kehityksen välisiä yhteyksiä kahden vanhemman perheissä painottaen erityisesti varhaisia isälapsisuhteita. Aineisto kerättiin osana monitieteistä Hyvän kasvun avaimet -kohorttitutkimusta. Perheitä (n = 153) seurattiin raskaudesta alkaen siihen asti, kunnes lapsi oli 18 kuukauden ikäinen. Tämän väitöskirjan tavoitteena oli tutkia 1) isän raskaudenaikaisten mielikuvien yhteyksiä isän ja lapsen väliseen vuorovaikutukseen (tutkimus I), 2) isän ja lapsen välisessä vuorovaikutuksessa tapahtuvia muutoksia ja pysyvyyttä vauvaiästä taaperoikään (tutkimus I), 3) vanhemman ja lapsen dyadisen vuorovaikutuksen ja perheen triadisen vuorovaikutuksen välisiä yhteyksiä (tutkimus II) ja 4) isien ja äitien raskaudenaikaisten mielikuvien yhteyksiä lapsen sosioemotionaaliseen kehitykseen (tutkimus III). Tulokset osoittivat, että isän tasapainoiset raskaudenaikaiset mielikuvat olivat yhteydessä laadukkaampaan isän ja vauvan väliseen vuorovaikutukseen. Isän ja lapsen välisessä vuorovaikutuksessa havaittiin sekä myönteisiä muutoksia että pysyvyyttä vauvaiästä taaperoikään. Hyvin toimiva vanhemman ja lapsen välinen vuorovaikutus, erityisesti isän ja lapsen välillä, oli yhteydessä perheen triadisen vuorovaikutuksen parempaan koordinaatioon ja kooperatiiviseen allianssiin taaperovaiheessa. Kummankin vanhemman tasapainoiset raskaudenaikaiset mielikuvat olivat lisäksi yhteydessä lapsen parempaan sosiaaliseen kompetenssiin. Tulokset korostavat tasapainoisten raskaudenaikaisten mielikuvien ja hyvin toimivien varhaisten vanhemman ja lapsen välisten suhteiden merkitystä. Sekä isä-lapsi- että äiti-lapsisuhteella on merkitystä perheen triadisen vuorovaikutuksen ja lapsen sosioemotionaalisen kehityksen näkökulmasta.